Improved polaronic transport under a strong Mott–Hubbard interaction in Cu-substituted NiO. Issue 4 (3rd December 2019) - Park, Seong Gon; Lee, Kyu Hyoung; Lee, Jae-Hoon; Bang, Geukchan; Kim, Junghwan; Park, Hee Jung; Oh, Min Suk; Lee, Suyoun; Kim, Young-Hoon; Kim, Young-Min; Hosono, Hideo; Bang, Joonho; et al.
Abstract : We report the origin of improved hole conduction without band-gap collapse in Cu-doped NiO. Abstract : The origin of the electrical and optical properties of Cu-substituted NiO (Cu : NiO) polycrystalline bulks synthesized via a solid-state reaction is reported. The partial substitution of Ni sites with Cu led to a drastic decrease of the electrical resistivity from 7.73 × 10 8 to 6.51 × 10 4 Ω·cm and a reduction in the energy for the self-trapping barrier from 0.58 to 0.24 eV in accordance with small polaron hopping conduction. The well-sustained band gap of 3.1 eV and antiferromagnetic transition temperature of 453 K demonstrate that the strength of the electron correlation in NiO can persist even at a high Cu concentration up to 22 atomic percent. Density functional theory calculations confirm that the Cu 3d orbital encourages d – p hybridization between metal cations and oxygen anions at the valence band maximum. As a consequence, this hybridization plays a critical role in improving the polaron hopping efficiency without much suppression of the Mott–Hubbard interaction and thus retaining the wide band gap nature.